Peran Kompetensi Sumber Daya Manusia dalam Peningkatan Produktivitas Pertenakan Sapi: Studi Kasus Desa Penungkiran Kec. Pancur Batu - Zainarti Zainarti; Adisty Aulia Zahra; Elvira Andriyani; Muhammad Iqbal; Popi Dea Ananda; Salsabila Sofiya Wardani (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
This research aims to analyze the role of human resource (HR) competency in increasing the productivity of cattle farming in Penungkiran Village, Pancur Batu District. This study was conducted on a farm owned by Mr. Syahdan Azis Maulana, a 25 yearold young farmer who manages 17 cows with the main aim of meeting economic needs. Through a qualitative approach, data was collected through in-depth interviews and direct observation. The research results show that HR competencies, including technical knowledge, managerial skills, and interpersonal abilities, have a significant impact on livestock productivity. Cattle sales can reach between 15 and 50 million per head, reflecting the potential for high profits if managed well. This research concludes that increasing human resource competency is a key factor in achieving optimal productivity in cattle farming.